Integrating Psychiatric Assessment in Chemical Castration Sanctions for Child Sexual Offenders in Indonesia - Y.A. Triana Ohoiwutun; Gio Arjuna Putra; Vicko Taniady (Sriwijaya Law Review, 2026)
Indonesian Law No. 17 of 2016 was enacted to aggravate sanctions with chemical castration sanctions for sexual offenders against children. Viewed from a psychological perspective, a paedophile can also commit this sexual crime, so it is certainly not appropriate to impose this sanction on the person found to be a paedophile. For these facts, this current study provides a solid understanding of why it is necessary to involve the psychiatrist in the legal process of sexual crimes against children. To achieve this understanding, the data were collected from the texts of the verdicts concerning sexual crimes against children issued by the Mojokerto District Court on 2 May 2019, the Surabaya District Court on 18 November 2019, and the Sumenep District Court on 9 December 2025. The collected data were then analysed using the model developed by Miles and Huberman (1994). The result of the analysis reveals that because of the lack of involvement of the psychiatrist in the legal process of sexual crime against children, the three verdicts does not state that the perpetrators of sexual crime against children are paedophiles. Therefore, it is necessary to involve the psychiatrist in the legal process of sexual crimes against children. From the perspective of comparative law, the involvement of psychiatrists in the implementation of chemical castration is manifested in two forms: firstly, providing opinions by considering the mental state of the Defendant (judicial process), and secondly, in the form of observation, monitoring, and post-chemical castration recommendations (as the executor of the Court's decision).